Efek Paparan Musik Klasik, Hard Rock dan Murottal Terhadap Pertumbuhan Vegetatif Tanaman Bayam Merah (Alternanthera amoena Voss) - Diah Wulandari Rousdy, Resti Elvi Rusmiyanto PW (Jurnal Protobiont, 2018)
This research was conducted to determine the effect of classical music, hard rock and murottal against to vegetative growing of red spinach plants. The research used a completely randomizes design with 4 treatments and 5 replicates. ANOVA result showed that music exposure had significant effect on plant growth. Murottal exposure gave optimal result on plant height 35,70 cm, leaf area 43,40 cm2, root length 9,40 cm, stomata porous length 23,00 µm, wet weigh 15,59 g, and dry weight of the plant 11,25 g. Exposure to hard rock music gives optimal results on the amount of leaf chlorophyll is worth 34,52 spad unit.